Underdetermined Dyson-Schwinger equations - Bender, Carl M.; Karapoulitidis, Christos; Klevansky, Sandra Pamela (Physical review letters, 2023)
This Letter examines the effectiveness of the Dyson-Schwinger (DS) equations as a calculational tool in quantum field theory. The DS equations are an infinite sequence of coupled equations that are satisfied exactly by the connected Green’s functions Gn of the field theory. These equations link lower to higher Green’s functions and, if they are truncated, the resulting finite system of equations is underdetermined. The simplest way to solve the underdetermined system is to set all higher Green’s function(s) to zero and then to solve the resulting determined system for the first few Green’s functions. The G1 or G2 so obtained can be compared with exact results in solvable models to see if the accuracy improves for high-order truncations. Five D=0 models are studied: Hermitian ϕ4 and ϕ6 and non-Hermitian iϕ3, −ϕ4, and iϕ5 theories. The truncated DS equations give a sequence of approximants that converge slowly to a limiting value but this limiting value always differs from the exact value by a few percent. More sophisticated truncation schemes based on mean-field-like approximations do not fix this formidable calculational problem.